Method for producing high-precision corrosion-resistant casting through shell mold casting and application of high-precision corrosion-resistant casting

By optimizing the coated sand formula and casting material composition, combined with process parameter optimization, the problems of insufficient corrosion resistance, dimensional accuracy and shell strength in shell casting have been solved, realizing the stable production of high-precision corrosion-resistant castings suitable for marine equipment and chemical equipment.

CN121131672APending Publication Date: 2025-12-16JIAHE FEIHENG ALLOY CASTING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511139986.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-14
Publication Date
2025-12-16

AI Technical Summary

Technical Problem

Existing shell casting processes suffer from insufficient corrosion resistance, low dimensional accuracy, and inadequate shell strength, making it difficult to meet the application requirements of high-end equipment.

Method used

By optimizing the coating sand formula and casting material composition, a coating sand composed of high-purity chromite sand, modified phenolic resin and nano alumina sol is used. Combined with the synergistic effect of multiple elements, process parameters such as heating temperature and pouring temperature are optimized. A vacuum environment and steel shot are used to compact the shell to form a dense passivation film and a stable casting structure.

Benefits of technology

It significantly improves the corrosion resistance, dimensional accuracy, and shell stability of castings, reduces production costs, and is suitable for marine equipment and chemical equipment in high-temperature and high-pressure corrosive environments, improving the thermal fatigue resistance and metallurgical quality of castings.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a method for producing a high-precision corrosion-resistant casting through shell mold casting and application of the method, and belongs to the technical field of casting. The method comprises the steps of shell mold manufacturing, shell boxing, melting casting and casting taking-out, specifically, precoated sand containing chromite sand, modified phenolic resin and the like is prepared, after shell manufacturing, steel shots are filled for compaction, molten iron containing C, Si, Ni, rare earth and the like is cast at the temperature of 1350-1400 DEG C, and after cooling, the casting is taken out and cleaned. According to the method, the corrosion resistance, the precision and the mechanical property of the casting are improved through material component collaboration and process optimization, and the method is suitable for the fields of pump valves, marine equipment and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of metal casting technology, specifically relating to a method for producing high-precision corrosion-resistant castings by shell casting and its application in pumps, valves, marine equipment and other fields. Background Technology

[0002] Casting, as a fundamental process in the machinery manufacturing field, directly impacts the performance and quality of high-end equipment. With the rapid development of marine engineering, petrochemicals, nuclear power, and other fields, increasingly stringent requirements are being placed on the corrosion resistance, dimensional accuracy, and mechanical properties of castings. Traditional casting methods face numerous technical bottlenecks in producing high-precision corrosion-resistant castings, making it difficult to meet practical application needs.

[0003] Shell casting, as a precision casting process, offers advantages such as high dimensional accuracy and good surface quality. However, it has significant shortcomings in improving corrosion resistance and adaptability to complex working conditions. Existing shell casting coating sand typically uses quartz sand as the main aggregate, combined with ordinary phenolic resin as a binder. During high-temperature casting, this sand is prone to thermal deformation and cracking, leading to defects such as shrinkage cavities and sand holes in the castings, severely affecting their density and corrosion resistance. Furthermore, traditional coating sand lacks effective reinforcing and lubricating components, resulting in low shell strength and poor permeability. This can cause problems such as flameout and sand adhesion during molten iron filling, reducing the surface quality and dimensional accuracy of the castings.

[0004] Regarding casting materials, while traditional cast iron materials possess excellent casting properties, their corrosion resistance and high-temperature stability are insufficient. In ordinary gray cast iron, the irregular morphology of graphite easily forms corrosion channels, making it highly susceptible to rusting in humid, saline, or acidic environments. Although ductile iron undergoes spheroidizing treatment to improve its mechanical properties, it still faces risks such as pitting corrosion and stress corrosion cracking in marine environments with high chloride ion concentrations. Existing corrosion-resistant cast irons often enhance corrosion resistance by adding alloying elements such as Cr and Ni. However, relying solely on alloying elements is not only costly, but also fails to fully leverage the synergistic effects between elements, making it difficult to form a stable and dense passivation film, thus limiting the corrosion resistance effect.

[0005] Furthermore, the existing shell casting process parameters lack systematic optimization. For example, the setting of key parameters such as shell heating temperature and pouring temperature is unreasonable, leading to incomplete solidification or excessive aging of the shell, poor fluidity and filling of the molten iron, and defects such as cold shuts and incomplete filling in the castings. At the same time, the shell lacks effective compaction and support measures during the packing process, making the shell prone to deformation under the impact of casting and cooling shrinkage, further reducing the dimensional accuracy of the castings.

[0006] In the field of marine equipment, castings such as pumps, valves, and pipelines are exposed to high salt spray and strong corrosive environments for extended periods. Traditional castings often require frequent replacement due to insufficient corrosion resistance, increasing maintenance costs and potentially leading to safety accidents. In the petrochemical industry, equipment such as reactors and heat exchangers have extremely high requirements for the high-temperature corrosion resistance and mechanical properties of castings. Castings produced using existing casting methods are prone to creep and corrosion failure in high-temperature, high-pressure corrosive media, severely impacting equipment operational safety and lifespan.

[0007] Therefore, developing a shell casting method that can synergistically optimize the properties of coated sand, the composition of casting materials, and process parameters to achieve stable production of high-precision corrosion-resistant castings has become a key technical problem urgently needing to be solved in the current casting field. This invention addresses the shortcomings of the existing technology by innovating the coated sand formula and optimizing the composition of casting materials and process parameters, significantly improving the corrosion resistance, dimensional accuracy, and mechanical properties of castings to meet the application needs of high-end equipment.

[0008] The above background information is provided only to aid in understanding the inventive concept and technical solution of this invention. It does not necessarily belong to the prior art of this patent application. In the absence of clear evidence that the above information was disclosed on the filing date of this patent application, the above background information should not be used to evaluate the novelty and inventiveness of this application. Summary of the Invention

[0009] The purpose of this invention is to provide a method for producing high-precision corrosion-resistant castings by shell casting and its application, so as to solve the technical problems of insufficient corrosion resistance, low dimensional accuracy and insufficient shell strength of castings in the existing shell casting process.

[0010] To achieve the above technical objectives, the present invention adopts the following technical solution:

[0011] A method for producing high-precision corrosion-resistant castings by shell casting includes the following steps:

[0012] S1. Shell Formation: Prepare coated sand and evenly cover it on a metal template. Heat the metal template to create the upper and lower shells. Then, bond and integrate the upper and lower shells to form a complete shell.

[0013] S2. Shell Packing: Place the prepared shell into the box, fill the gap between the outside of the shell and the inner wall of the box with steel shot, and use vibration to make the steel shot fully compacted.

[0014] S3, Melting and Casting: The casting material is melted into molten iron under vacuum and poured into the inner cavity of the shell mold. After pouring, it is cooled to form the casting.

[0015] S4. Casting Removal: Pour out the castings, waste sand, and steel shot from the box. After separating the castings, clean and inspect the surface of the castings. Once qualified, they are put into storage.

[0016] Preferably, the casting material composition, by mass percentage, includes: C: 2.5-3.5%, Si: 2.5-3.5%, Mn: 0.6-0.8%, Ni: 0.5-1.0%, Cu: 1.0-1.5%, Mo: 0.3-0.5%, Cr: 3-5%, N: 0.05-0.1%, S≤0.1%, P≤0.15%, total rare earth elements 0.1-0.5%, with the balance being Fe; wherein the rare earth elements include Y, Ce, La, and Nd, wherein N is added in the form of chromium nitride intermediate alloy.

[0017] Preferably, the mass percentage of each component in the rare earth elements is as follows: Y accounts for 30-40% of the total rare earth, Ce accounts for 35-45%, La accounts for 10-20%, and Nd accounts for 10-20%.

[0018] Preferably, in step S1, the coated sand comprises, by mass percentage: 80-90% chromite sand, 6-7% modified phenolic resin, 2.5-3.5% nano-alumina sol, 1.0-1.5% hexagonal boron nitride, 0.7-1.0% titanate coupling agent, 1.5-2.5% silicon carbide whiskers, 1.2-1.8% yttrium-stabilized zirconium oxide, 0.4-0.8% zinc stearate, and 0.3-0.5% hydroquinone.

[0019] Preferably, the particle size of the chromite sand is 50-200 mesh.

[0020] Preferably, in step S3, during the process of melting into molten iron, a medium-frequency induction furnace is used for heating, and the heating rate is 50-80℃ / min.

[0021] Preferably, in step S1, the heating temperature of the metal template is controlled at 170-290℃.

[0022] Preferably, in step S3, the pouring temperature of the molten iron is controlled at 1350-1400℃.

[0023] Preferably, in step S2, the particle size of the steel shot is 0.5-2 mm.

[0024] This invention also provides the application of the above method in the production of chemical equipment parts and marine engineering equipment parts.

[0025] Technical principle:

[0026] The roles and synergistic mechanisms of the components in casting materials:

[0027] Carbon (C): As a key element in cast iron, it can improve the fluidity of molten iron and promote graphitization. In this invention, C and Si work synergistically. Si promotes the graphitization process, making it easier for C to form uniformly distributed graphite, reducing the brittleness of carbides, and ensuring good filling capacity of molten iron during casting, thus avoiding incomplete filling defects in the casting.

[0028] Silicon (Si): Not only does it promote graphitization and reduce the tendency for white iron, but it can also synergistically enhance the oxidation resistance of castings with rare earth elements. Si increases the electrode potential of the iron matrix and works with Ni and Cu to form a more stable passivation film, improving corrosion resistance; at the same time, Si, in combination with Mo, enhances the creep resistance of castings at high temperatures.

[0029] Manganese (Mn): Its main function is to neutralize the harmful effects of sulfur (S), forming MnS inclusions and avoiding the hot brittleness caused by FeS. Mn can also refine the pearlite structure, synergistically promoting pearlite formation with Cu, improving the strength and wear resistance of castings, and creating conditions for the uniform distribution of elements such as Ni and Mo in the matrix.

[0030] Nickel (Ni): Stabilizes austenitic structure and improves corrosion resistance. Ni works synergistically with Cu, where Cu promotes pearlite formation and Ni enhances the passivation ability of the matrix, together improving the corrosion resistance of castings in acidic and alkaline environments. At the same time, Ni works with rare earth elements Y and Ce, where the oxide film formed by Y bonds more tightly with the passivation film of Ni, improving the stability of the corrosion-resistant film.

[0031] Copper (Cu): Promotes pearlite formation, increases hardness and strength, and enhances resistance to atmospheric corrosion. Cu works synergistically with Mo, where the carbide strengthening effect of Mo combines with the solid solution strengthening effect of Cu to improve the mechanical properties of castings. Simultaneously, Cu improves machinability, and in conjunction with the free-machining effect of S, reduces cutting resistance.

[0032] Molybdenum (Mo): Forms stable carbides, improving high-temperature strength and creep resistance. Mo works synergistically with Si, where Si enhances high-temperature oxidation resistance, while Mo strengthens structural stability at high temperatures. Together, they improve the performance of castings under high-temperature conditions. Simultaneously, Mo, in combination with Ni, enhances resistance to pitting corrosion, especially in chloride-containing environments.

[0033] Chromium (Cr): As a core element for corrosion resistance, Cr can form a dense Cr2O3 passivation film on the surface of castings, effectively blocking the intrusion of corrosive media. In combination with Ni, it can further stabilize the passivation film structure and improve corrosion resistance in oxidizing media. At the same time, Cr combines with N to form chromium nitride (CrN), which refines grains and strengthens grain boundaries, reducing the risk of intergranular corrosion. When combined with Mo, it can also enhance the resistance to chloride ion corrosion, making it particularly suitable for harsh environments such as marine and chemical industries.

[0034] Nitrogen (N): Introduced through chromium nitride master alloys, it synergistically forms chromium nitride (CrN) with chromium, enhancing the density of the surface oxide film, effectively isolating oxygen and corrosive media, and significantly improving resistance to intergranular corrosion, pitting corrosion, and crevice corrosion. Simultaneously, N stabilizes the austenite structure, reducing intermetallic phase precipitation and further optimizing corrosion resistance. In high-temperature, high-pressure, or chloride-containing environments, the addition of N can significantly enhance the corrosion resistance of materials, but the content must be strictly controlled between 0.05-0.1%, avoiding exceeding 0.16% as it damages the oxide protective layer and leads to deterioration of oxidation resistance.

[0035] Sulfur (S): A small amount of S improves machinability and works synergistically with Cu to make the cutting process smoother. However, the content must be strictly controlled to avoid forming a low-melting-point eutectic with Fe, which would lead to hot cracking. The presence of Mn can effectively neutralize the harmful effects of S, forming stable MnS.

[0036] Phosphorus (P): Appropriate amounts of P improve the fluidity of molten iron and work synergistically with C and Si to improve casting performance. However, excessive amounts can form brittle phosphorus eutectics. Therefore, the content should be controlled to balance casting performance and mechanical properties.

[0037] Rare earth elements (Y, Ce, La, Nd): Y forms a dense Y₂O₃ oxide film, which synergizes with the passivation films of Ni and Cu to improve corrosion resistance; Ce purifies grain boundaries and, together with La, refines the microstructure and reduces corrosion channels; La promotes graphite spheroidization and, together with Nd, enhances high-temperature stability; Nd can also combine with Mo to improve creep resistance. Overall, rare earth elements work synergistically with other alloying elements to optimize the microstructure of castings and improve overall performance.

[0038] Iron (Fe): As the matrix, it supports the functions of other elements. Its purity is affected by other elements. The reasonable ratio of each element ensures the continuity and stability of the Fe matrix, providing a basis for synergistic effects.

[0039] The role and synergistic mechanism of each component in coated sand:

[0040] Chromite sand: It has a large heat capacity, which can more effectively play a role in rapid cooling, enhance the density of the surface structure of the casting, and prevent pitting corrosion on the surface of the casting; at the same time, it enhances the refractory properties of the shell mold, and its iron content has good compatibility with molten iron, reducing sand adhesion defects.

[0041] Modified phenolic resin: As a binder, it binds aggregates into shape. After modification, the thermal decomposition temperature is increased. In synergy with nano alumina sol, the sol fills the gaps in the resin, forming a denser bonding network, which enhances the shell strength and high temperature resistance.

[0042] Nano-alumina sol: Nanoparticles fill the gaps between aggregate and resin, increasing shell density; synergistically with yttrium-stabilized zirconia, they form a high-temperature resistant ceramic phase, enhancing thermal shock resistance and reducing shell cracking during casting.

[0043] Hexagonal boron nitride: It has a lubricating effect, reduces the frictional resistance during molten iron filling, and works synergistically with titanate coupling agents. The coupling agents improve the compatibility of hexagonal boron nitride with other components, making the lubrication effect more uniform and improving the fluidity of molten iron.

[0044] Titanate coupling agent: improves the interfacial bonding force between inorganic aggregates and organic resins, promotes uniform dispersion of each component, enhances the overall strength of the shell, and works synergistically with silicon carbide whiskers to improve the toughness and impact resistance of the shell.

[0045] Silicon carbide whiskers enhance the flexural strength and toughness of the shell. The whiskers form a network structure in the shell and work together with nano-alumina sol to buffer thermal shock and reduce cracks in the shell caused by temperature changes.

[0046] Yttrium-stabilized zirconia: It has excellent thermal shock resistance. In synergy with chromite sand, it improves the dimensional stability of the shell at high temperatures, reduces deformation caused by thermal expansion, and ensures the dimensional accuracy of the casting.

[0047] Zinc stearate: As a lubricant, it improves the fluidity of coated sand, facilitating uniform coverage during shell molding. In synergy with hexagonal boron nitride, it further reduces friction and improves the quality of shell molding.

[0048] Hydroquinone: As an inhibitor of resin curing, it controls the curing speed and works synergistically with modified phenolic resin to ensure that the shell is fully cured during heating without excessive aging, thus stabilizing the shell performance.

[0049] Method for preparing coated sand:

[0050] (1) Sand pretreatment: Dry the chromite sand at 250-270℃ for 100-140 min to control the moisture content to ≤0.3%.

[0051] (2) Surface activation treatment: The sand particles preheated to 75-85℃ are mixed with the titanate coupling agent in a high-speed sand mixer with a speed of 400-500 rpm and a treatment time of 7-9 min.

[0052] (3) Resin coating: Add modified phenolic resin preheated to 55-65℃, maintain the temperature of the sand mixer at 73-77℃, and mix sand for 13-17 minutes until the sand particles are evenly coated.

[0053] (4) Nano-strengthening: Add nano alumina sol in three batches, with an interval of 2-4 minutes between each batch, while controlling the pH value of the system at 8.3-9.2.

[0054] (5) Introduction of functional additives: Add hexagonal boron nitride, silicon carbide whiskers and yttrium oxide stabilized zirconium oxide powder in sequence, cool the sand mixer to 48-52℃ and mix for 18-22 minutes.

[0055] (6) Finished product processing: Finally, add zinc stearate and hydroquinone, mix at a low speed of 160-200 rpm for 8-12 minutes at 38-42℃, and then pass through a 65-75 mesh sieve to obtain the final product.

[0056] Materials for preparing modified phenolic resin:

[0057] 485.0±2.0g industrial grade phenol (purity ≥99.5%), 612.0±3.0g 37% formaldehyde solution, 8.7±0.2g analytical grade granular sodium hydroxide, 22.5±0.5g nanocellulose crystals, 15.8±0.3g KH-550 silane coupling agent, 9.3±0.2g polyvinyl butyral, 4.2±0.1g crystalline oxalic acid (purity ≥99%), and deionized water and ethanol for dispersion and dissolution.

[0058] Preparation method of modified phenolic resin:

[0059] (1) Synthesis of alkaline prepolymer: Phenol was added to a 2000ml four-necked flask, and the temperature was raised to 65±1℃ in a water bath. Sodium hydroxide dissolved in 50±2ml deionized water was slowly added dropwise (temperature controlled ≤70℃). Formaldehyde solution was then added at a rate of 2±0.2ml / min, and the pH was maintained at 8.5-9.0. The reaction was carried out at 85±1℃ for 120±5min until the viscosity reached 300-350cP, thus obtaining the alkaline prepolymer.

[0060] (2) Nanocellulose modification: Nanocellulose and KH-550 were ultrasonically dispersed in an ethanol / water mixture at a volume ratio of 7:3 at 300W for 30±2min. The dispersion was then added to the prepolymer and stirred at 200±10rpm at 75±1℃ for 90±5min to complete the nanomodification.

[0061] (3) PVB toughening treatment: Add polyvinyl butyral, heat to 90±1℃, and dehydrate under vacuum of -0.095±0.002MPa until the resin is transparent (moisture content ≤2.5%).

[0062] (4) Acid curing: Cool down to 60±1℃, add oxalic acid dissolved in 20±1ml ethanol, react at 80±1℃ for 45±3min until the gelation time reaches 90-100s at 150℃;

[0063] (5) Post-treatment: Cool to 25±2℃, adjust pH to 6.8-7.2, filter through a 200-mesh sieve and then seal for storage. The shelf life of the finished product is ≥6 months.

[0064] The beneficial effects of this invention compared to the prior art include:

[0065] 1. Significantly improves the corrosion resistance of castings

[0066] In existing technologies, improving the corrosion resistance of castings often relies on a single alloying element, making it difficult to form a stable passivation film. This invention significantly enhances corrosion resistance through the synergistic effect of multiple elements. In the casting material, Ni and Cu can increase the electrode potential of the substrate, forming a preliminary passivation layer; Mo promotes passivation film repair and enhances resistance to pitting corrosion; Cr combines with N to form chromium nitride (CrN), strengthening the density of the oxide film; rare earth element Y forms a dense Y₂O₃ oxide film; Ce, La, and Nd purify grain boundaries, refine the microstructure, and reduce corrosion channels. The synergistic effect of these elements makes the passivation film more stable and complete, significantly enhancing its resistance to salt spray corrosion.

[0067] 2. Improve the dimensional accuracy of castings

[0068] Traditional shell casting suffers from large dimensional tolerances due to shell thermal deformation and unstable process parameters. This invention improves precision through both coated sand formulation and process optimization. The coated sand uses high-purity chromite sand with a reasonable particle size distribution, resulting in excellent shell dimensional stability. Modified phenolic resin and nano-alumina sol enhance shell strength and reduce the coefficient of thermal expansion. In terms of process, the heating temperature of the metal mold is controlled between 170-290℃ to ensure full curing of the shell without excessive aging. The shell is packed tightly with steel shot, and vacuum casting reduces impact deformation. The final casting dimensional tolerance can be controlled within ±0.1mm, meeting the requirements of high-precision equipment, such as improved sealing surface precision in pumps and valves, and reduced leakage.

[0069] 3. Enhanced high-temperature stability of the shell

[0070] Existing coated sand is prone to shell collapse when casting molten iron at temperatures above 1300℃ due to insufficient aggregate refractoriness and binder decomposition. The coated sand of this invention uses high-refractory chromite sand, capable of withstanding molten iron temperatures of 1350-1400℃; modified phenolic resin, modified with nano-cellulose and PVB, has an increased thermal decomposition temperature; nano-alumina sol and yttrium-stabilized zirconium oxide form a high-temperature resistant ceramic network structure, enhancing the shell's thermal shock resistance. During casting, the shell remains crack-free and does not collapse, effectively avoiding sand adhesion and sand hole defects in the casting, thus improving the casting yield.

[0071] 4. Improves the fluidity of molten iron and the density of castings

[0072] Poor fluidity of molten iron can lead to incomplete casting and cold shuts, while low density reduces mechanical properties and corrosion resistance. This invention improves upon these issues through both materials and processes: optimized C and Si content in the casting material synergistically enhances molten iron fluidity; hexagonal boron nitride in the coated sand reduces resistance to molten iron filling. In terms of process, the pouring temperature is controlled at 1350-1400℃, and a vacuum environment is used to expel gases from the mold cavity, ensuring full filling of the molten iron; steel shot filling applies uniform pressure to the shell mold, providing effective support during casting cooling and shrinkage, reducing shrinkage porosity and gas buildup. The resulting casting has high density and enhanced tensile strength.

[0073] 5. Optimize the machinability of castings

[0074] Corrosion-resistant castings, due to their high alloy content, are often difficult to machine and suffer from severe tool wear. This invention improves machinability through composition optimization: an appropriate amount of sulfur forms easily machinable MnS inclusions, reducing cutting resistance; copper improves the uniformity of the cast iron microstructure, making the cutting process smoother; and titanate coupling agents enhance the wettability of the coated sand-metal interface, reducing the surface roughness (Ra) of the casting and decreasing cutting friction and wear. Compared to traditional corrosion-resistant castings, the castings produced by this invention have a smoother cutting process, extended tool life, and contribute to reduced production costs.

[0075] 6. Reduce production costs

[0076] Current methods for producing high corrosion-resistant castings often combine precision casting with surface treatment, resulting in high costs. This invention achieves high corrosion resistance without additional surface treatment through synergistic material and process optimization: rare earth elements and nitrogen in the casting material work synergistically, reducing the amount of precious metal Ni required. Compared to traditional methods, this approach offers significant cost advantages and increased production efficiency, making it suitable for large-scale industrial production.

[0077] 7. Enhances the thermal fatigue resistance of castings

[0078] Under alternating hot and cold operating conditions, castings are prone to cracking due to thermal stress. This invention improves thermal fatigue resistance in several ways: Si in the casting material enhances thermal fatigue resistance, rare earth element La promotes graphite spheroidization, and reduces stress concentration; silicon carbide whiskers in the coated sand enhance shell toughness and buffer thermal shock during casting. After multiple hot and cold cycle tests, castings made with this invention showed no cracks, while traditional castings developed obvious cracks after the same number of cycles. This invention is suitable for environments with large temperature variations, such as ship engine blocks and chemical reactor components.

[0079] 8. Improve material purity and metallurgical quality

[0080] This invention significantly reduces the content of impurities and harmful gases in materials through the synergistic effect of vacuum casting and materials / processes. In a vacuum environment, the molten iron melting and casting process minimizes contact time with the atmosphere, effectively preventing the intrusion of gases such as oxygen, nitrogen, and hydrogen, and reducing defects such as porosity and inclusions. Simultaneously, the purification effect of rare earth elements, due to the adsorption of non-metallic inclusions by Ce and La, combined with the synergistic enhancement of Cr and N, further reduces the negative impact of harmful elements such as sulfur and phosphorus. The improved material purity leads to more stable metallurgical quality in the castings, not only reducing the channels for corrosive media to diffuse along impurities but also enhancing matrix uniformity, ensuring the continuous formation of a passivation film, and fundamentally improving the corrosion resistance and mechanical stability of the castings. Detailed Implementation

[0081] I. Preparation Method

[0082] 1. Material preparation

[0083] Casting material: C: 2.5-3.5%, Si: 2.5-3.5%, Mn: 0.6-0.8%, Ni: 0.5-1.0%, Cu: 1.0-1.5%, Mo: 0.3-0.5%, Cr: 3-5%, N: 0.05-0.1%, S≤0.1%, P≤0.15%, total rare earth elements 0.1-0.5%, balance Fe; wherein the rare earth elements include Y, Ce, La, and Nd, wherein N is added in the form of chromium nitride intermediate alloy.

[0084] Materials for preparing coated sand: 80-90% chromite sand, 6-7% modified phenolic resin, 2.5-3.5% nano-alumina sol, 1.0-1.5% hexagonal boron nitride, 0.7-1.0% titanate coupling agent, 1.5-2.5% silicon carbide whiskers, 1.2-1.8% yttrium-stabilized zirconium oxide, 0.4-0.8% zinc stearate, and 0.3-0.5% hydroquinone. The chromite sand particle size is 50-200 mesh.

[0085] Materials used to prepare the modified phenolic resin: 485.0±2.0g industrial grade phenol (purity ≥99.5%), 612.0±3.0g 37% formaldehyde solution, 8.7±0.2g analytical grade granular sodium hydroxide, 22.5±0.5g nanocellulose crystals, 15.8±0.3g KH-550 silane coupling agent, 9.3±0.2g polyvinyl butyral, 4.2±0.1g crystalline oxalic acid (purity ≥99%), and deionized water and ethanol for dispersion and dissolution.

[0086] Steel shot: 0.5-2mm in diameter.

[0087] 2. Shell molding

[0088] Prepare the coated sand and evenly cover it on the metal template. Use medium-frequency induction heating to heat the metal template. The heating temperature can be selected within the range of 170-290℃ according to actual needs to create the upper shell and the lower shell. Then use an adhesive to bond and integrate the upper and lower shells to form a complete shell.

[0089] 3. Packing the outer casing

[0090] The prepared shell mold is placed into the box, and steel shot is filled into the gap between the outer shell mold and the inner wall of the box. The steel shot is then fully compacted by vibration equipment to enhance the stability of the shell mold during the casting process.

[0091] 4. Melting and casting

[0092] The prepared casting material is placed in a medium-frequency induction furnace and heated to a molten state at a heating rate of 50-80℃ / min to obtain molten iron. The entire gating system is evacuated (vacuum degree ≤0.095MPa), and the molten iron is poured into the inner cavity of the shell mold at a temperature of 1350-1400℃ under vacuum. After pouring, the casting is allowed to cool naturally to form the casting.

[0093] 5. Removal of castings

[0094] After the castings have cooled to room temperature, the castings, waste sand, and steel shot inside the box are poured out together. The castings are then separated using methods such as sieving. The surface of the castings is then sandblasted at a pressure of 0.3-0.5 MPa with sand particles of 0.1-0.3 mm in diameter to remove residual sand and oxide scale. After separation, the castings are cleaned, inspected, and then stored in the warehouse if they pass inspection.

[0095] 6. Preparation of coated sand

[0096] (1) Pretreatment of sand particles: Dry the chromite sand at 260℃ for 120 min to control the moisture content to ≤0.3%;

[0097] (2) Surface activation treatment: The sand particles preheated to 80°C are mixed with the titanate coupling agent in a high-speed sand mixer at a speed of 450 rpm for 8 min.

[0098] (3) Resin coating: Add modified phenolic resin preheated to 60℃, maintain the temperature of the sand mixer at 75±2℃, and mix sand for 15 minutes until the sand particles are evenly coated.

[0099] (4) Nano-strengthening: Add nano alumina sol in three batches, with an interval of 3 minutes between each batch, while controlling the pH of the system at 8.5-9.0;

[0100] (5) Introduction of functional additives: Hexagonal boron nitride, silicon carbide whiskers and yttrium oxide stabilized zirconium oxide powder are added in sequence, the sand mixer is cooled to 50°C and mixed for 20 min;

[0101] (6) Finished product processing: Finally, add zinc stearate and hydroquinone, mix at 180 rpm for 10 min at 40°C, and then pass through a 70-mesh sieve to obtain the final product.

[0102] 7. Preparation of modified phenolic resin

[0103] (1) Synthesis of alkaline prepolymer: Phenol was added to a 2000ml four-necked flask, and the temperature was raised to 65±1℃ in a water bath. Sodium hydroxide dissolved in 50±2ml deionized water was slowly added dropwise (temperature controlled ≤70℃). Formaldehyde solution was then added at a rate of 2±0.2ml / min, and the pH was maintained at 8.5-9.0. The reaction was carried out at 85±1℃ for 120±5min until the viscosity reached 300-350cP, thus obtaining the alkaline prepolymer.

[0104] (2) Nanocellulose modification: Nanocellulose and KH-550 were ultrasonically dispersed in an ethanol / water mixture at a volume ratio of 7:3 at 300W for 30±2min. The dispersion was then added to the prepolymer and stirred at 200±10rpm at 75±1℃ for 90±5min to complete the nanomodification.

[0105] (3) PVB toughening treatment: Add polyvinyl butyral, heat to 90±1℃, and dehydrate under vacuum of -0.095±0.002MPa until the resin is transparent (moisture content ≤2.5%).

[0106] (4) Acid curing: Cool down to 60±1℃, add oxalic acid dissolved in 20±1ml ethanol, react at 80±1℃ for 45±3min until the gelation time reaches 90-100s at 150℃;

[0107] (5) Post-treatment: Cool to 25±2℃, adjust pH to 6.8-7.2, filter through a 200-mesh sieve and then seal for storage. The shelf life of the finished product is ≥6 months.

[0108] The present invention will be further described in detail below with reference to specific embodiments. It should be emphasized that the following description is merely exemplary and is not intended to limit the scope and application of the present invention.

[0109] II. Implementation Examples

[0110] 1. Example 1

[0111] Shell making: Prepare coated sand and make the shell at a temperature of 240℃.

[0112] Shell packing: steel shot diameter 1.5mm, vibration compaction for 40s.

[0113] Melting and casting: Casting material: C: 3.0%, Si: 3.0%, Mn: 0.6%, Ni: 1.3%, Cu: 1.2%, Mo: 0.5%, S: 0.10%, P: 0.12%, Y: 0.08%, Ce: 0.10%, La: 0.03%, Nd: 0.02%, total rare earth 0.23%; 0.6% chromium nitride (N content 0.07%) added, balance Fe, heating rate 60℃ / min, vacuum degree 0.09MPa, pouring temperature 1370℃, vacuum holding pressure 12min.

[0114] Casting removal: Sandblasting pressure 0.4MPa, sand particle diameter 0.2mm.

[0115] Coated sand formulation: 83% 100-mesh chromite sand, 6.5% modified phenolic resin, 3.5% nano alumina sol, 1.5% hexagonal boron nitride, 0.8% titanate coupling agent, 2.0% silicon carbide whiskers, 1.5% yttrium-stabilized zirconium oxide, 0.7% zinc stearate, and 0.5% hydroquinone.

[0116] Preparation of coated sand:

[0117] (1) Pretreatment of sand particles: The chromite sand was dried at 260℃ for 120 min to control the moisture content to ≤0.3%;

[0118] (2) Surface activation treatment: preheated sand particles to 80°C are mixed with titanate coupling agent in a high-speed sand mixer at a speed of 450 rpm for 8 min.

[0119] (3) Resin coating: Add modified phenolic resin preheated to 60°C, maintain the temperature of the sand mixer at 75°C, and mix the sand for 15 minutes until the sand particles are evenly coated.

[0120] (4) Nano-strengthening: Nano alumina sol was added in three batches, with a 3-minute interval between each batch, while the pH of the system was controlled at 9.0.

[0121] (5) Functional additives are introduced by adding hexagonal boron nitride, silicon carbide whiskers and yttrium oxide stabilized zirconium oxide powder in sequence, cooling the sand mixer to 50°C and mixing for 20 minutes;

[0122] (6) Finished product processing: Finally, add zinc stearate and hydroquinone, mix at 180 rpm for 10 min at 40°C, and then pass through a 70-mesh sieve to obtain the final product.

[0123] Materials used to prepare the modified phenolic resin: 485.0 g industrial grade phenol (purity ≥99.5%), 612.0 g 37% formaldehyde solution, 8.7 g analytical grade granular sodium hydroxide, 22.5 g nano-cellulose crystals, 15.8 g KH-550 silane coupling agent, 9.3 g polyvinyl butyral, 4.2 g crystalline oxalic acid (purity ≥99%), and deionized water and ethanol for dispersion and dissolution.

[0124] Preparation of modified phenolic resin:

[0125] (1) Synthesis of alkaline prepolymer: Phenol was added to a 2000ml four-necked flask, the temperature was raised to 65℃ in a water bath, sodium hydroxide dissolved in 50ml deionized water was slowly added dropwise (temperature controlled ≤70℃), and formaldehyde solution was added at a rate of 2ml / min. The pH was maintained at 8.5-9.0, and the reaction was carried out at 85℃ for 120min until the viscosity reached 300cP (25℃) to obtain the alkaline prepolymer;

[0126] (2) Nanocellulose modification: Nanocellulose and KH-550 silane coupling agent were ultrasonically dispersed in a 7:3 volume ratio ethanol / water mixture for 30 min at a power of 300W. The dispersion was then added to the prepolymer and stirred at 200 rpm for 90 min at 75℃ to complete the nano-modification.

[0127] (3) PVB toughening treatment: add polyvinyl butyral, heat to 90℃, and dehydrate under -0.095MPa vacuum until the resin is transparent;

[0128] (4) Acid curing: Cool down to 60°C, add oxalic acid dissolved in 20ml ethanol, react at 80°C for 45min to 150°C for 90s gel time;

[0129] (5) Post-treatment: Cool to 25°C, adjust pH to 7.0, filter through a 200-mesh sieve and then seal for storage.

[0130] 2. Example 2

[0131] Shell making: Prepare coated sand and make the shell at a temperature of 240℃.

[0132] Shell packing: steel shot diameter 1.5mm, vibration compaction for 40s.

[0133] Melt casting: Casting material formula (wt%): C: 3.3%, Si: 2.8%, Mn: 0.8%, Ni: 1.0%, Cu: 1.5%, Mo: 0.3%, S: 0.08%, P: 0.10%, Y: 0.06%, Ce: 0.10%, La: 0.02%, Nd: 0.02%, total rare earth 0.20%; 0.5% chromium nitride (N content 0.06%) added, balance Fe. Heating rate 60℃ / min, vacuum degree 0.092MPa, pouring temperature 1370℃, vacuum holding pressure 10min.

[0134] Casting removal: Sandblasting pressure 0.4MPa, sand particle diameter 0.2mm.

[0135] Coated sand formulation (wt%): 100 mesh chromite sand 81.8%, modified phenolic resin 7%, nano alumina sol 3.5%, hexagonal boron nitride 1.2%, titanate coupling agent 1.0%, silicon carbide whiskers 2.5%, yttrium oxide stabilized zirconium oxide 1.8%, zinc stearate 0.7%, hydroquinone 0.5%.

[0136] The preparation of the coated sand, the materials for preparing the modified phenolic resin, and the preparation of the modified phenolic resin are the same as in Example 1.

[0137] 3. Example 3

[0138] Shell making: Prepare coated sand and make the shell at a temperature of 240℃.

[0139] Shell packing: steel shot diameter 1.5mm, vibration compaction for 40s.

[0140] Melt casting: Casting material formulation (wt%): C: 3.1%, Si: 3.2%, Mn: 0.7%, Ni: 1.1%, Cu: 1.3%, Mo: 0.4%, S: 0.09%, P: 0.13%, Y: 0.10%, Ce: 0.12%, La: 0.03%, Nd: 0.02%, total rare earth 0.27%; 0.8% chromium nitride (N content 0.09%) added, balance Fe. Heating rate 60℃ / min, vacuum degree 0.095MPa, pouring temperature 1370℃, vacuum holding pressure 15min.

[0141] Casting removal: Sandblasting pressure 0.4MPa, sand particle diameter 0.2mm.

[0142] Coated sand formulation (wt%): 84% 100-mesh chromite sand, 6.5% modified phenolic resin, 3.0% nano alumina sol, 1.2% hexagonal boron nitride, 0.8% titanate coupling agent, 2.0% silicon carbide whiskers, 1.5% yttrium-stabilized zirconium oxide, 0.6% zinc stearate, and 0.4% hydroquinone.

[0143] The preparation of the coated sand, the materials for preparing the modified phenolic resin, and the preparation of the modified phenolic resin are the same as in Example 1.

[0144] 4. Example 4

[0145] Shell making: Prepare coated sand and make the shell at a temperature of 240℃.

[0146] Shell packing: steel shot diameter 1.5mm, vibration compaction for 40s.

[0147] Melt casting: Casting material formula (wt%): C: 3.2%, Si: 3.5%, Mn: 0.65%, Ni: 1.2%, Cu: 1.1%, Mo: 0.45%, S: 0.11%, P: 0.14%, Y: 0.09%, Ce: 0.11%, La: 0.03%, Nd: 0.02%, total rare earth 0.25%; 0.7% chromium nitride (N content 0.08%) added, balance Fe. Heating rate 60℃ / min, vacuum degree 0.093MPa, pouring temperature 1370℃, vacuum holding pressure 13min.

[0148] Casting removal: Sandblasting pressure 0.4MPa, sand particle diameter 0.2mm.

[0149] Coated sand formulation (wt%): 82% 100-mesh chromite sand, 6.9% modified phenolic resin, 3.3% nano alumina sol, 1.5% hexagonal boron nitride, 0.9% titanate coupling agent, 2.5% silicon carbide whiskers, 1.7% yttrium oxide stabilized zirconium oxide, 0.8% zinc stearate, and 0.4% hydroquinone.

[0150] The preparation of the coated sand, the materials for preparing the modified phenolic resin, and the preparation of the modified phenolic resin are the same as in Example 1.

[0151] 5. Example 5

[0152] Shell making: Prepare coated sand and make the shell at a temperature of 240℃.

[0153] Shell packing: steel shot diameter 1.5mm, vibration compaction for 40s.

[0154] Melt casting: Casting material formula (wt%): C: 3.05%, Si: 2.6%, Mn: 0.75%, Ni: 1.05%, Cu: 1.4%, Mo: 0.35%, S: 0.07%, P: 0.11%, Y: 0.07% (32%), Ce: 0.10% (45%), La: 0.03% (14%), Nd: 0.03% (9%), total rare earth 0.23%; 0.6% chromium nitride (N content 0.07%) added, balance Fe. Heating rate 60℃ / min, vacuum degree 0.091MPa, pouring temperature 1370℃, vacuum holding pressure 11min.

[0155] Casting removal: Sandblasting pressure 0.4MPa, sand particle diameter 0.2mm.

[0156] Coated sand formulation (wt%): 83% 100-mesh chromite sand, 6.8% modified phenolic resin, 3.2% nano alumina sol, 1.4% hexagonal boron nitride, 1% titanate coupling agent, 2.2% silicon carbide whiskers, 1.2% yttrium-stabilized zirconium oxide, 0.7% zinc stearate, and 0.5% hydroquinone.

[0157] The preparation of the coated sand, the materials for preparing the modified phenolic resin, and the preparation of the modified phenolic resin are the same as in Example 1.

[0158] II. Comparative Example

[0159] 1. Comparative Example 1

[0160] The difference from Example 3 is that the casting material does not contain rare earth elements and chromium nitride, and it is not vacuum casting (atmospheric pressure environment), while the other conditions are the same.

[0161] The parameters for shell fabrication, shell packing, and casting removal are the same as in Example 3.

[0162] Shell making: Prepare coated sand and make the shell at a temperature of 240℃.

[0163] Shell packing: steel shot diameter 1.5mm, vibration compaction for 40s.

[0164] Melt casting: Casting material formula (wt%): C: 3.1%, Si: 3.2%, Mn: 0.7%, Ni: 1.1%, Cu: 1.3%, Mo: 0.4%, S: 0.09%, P: 0.13%; balance Fe. Heating rate: 60℃ / min, pouring temperature: 1370℃.

[0165] Casting removal: Sandblasting pressure 0.4MPa, sand particle diameter 0.2mm.

[0166] Coated sand formulation (wt%): 84% 100-mesh chromite sand, 6.5% modified phenolic resin, 3.0% nano alumina sol, 1.2% hexagonal boron nitride, 0.8% titanate coupling agent, 2.0% silicon carbide whiskers, 1.5% yttrium-stabilized zirconium oxide, 0.6% zinc stearate, and 0.4% hydroquinone.

[0167] The preparation of the coated sand, the materials for preparing the modified phenolic resin, and the preparation of the modified phenolic resin are the same as in Example 1.

[0168] 2. Comparative Example 2

[0169] The difference from Example 3 is that the coated sand is made of quartz sand instead of chromite sand, while the other conditions (including vacuum casting) are the same.

[0170] Shell making: Prepare coated sand and make the shell at a temperature of 240℃.

[0171] Shell packing: steel shot diameter 1.5mm, vibration compaction for 40s.

[0172] Melt casting: Casting material formulation (wt%): C: 3.1%, Si: 3.2%, Mn: 0.7%, Ni: 1.1%, Cu: 1.3%, Mo: 0.4%, S: 0.09%, P: 0.13%, Y: 0.10%, Ce: 0.12%, La: 0.03%, Nd: 0.02%, total rare earth 0.27%; 0.8% chromium nitride (N content 0.09%) added, balance Fe. Heating rate 60℃ / min, vacuum degree 0.095MPa, pouring temperature 1370℃, vacuum holding pressure 15min.

[0173] Casting removal: Sandblasting pressure 0.4MPa, sand particle diameter 0.2mm.

[0174] Coated sand formulation (wt%): 84% 100-mesh quartz sand, 6.5% modified phenolic resin, 3.0% nano alumina sol, 1.2% hexagonal boron nitride, 0.8% titanate coupling agent, 2.0% silicon carbide whiskers, 1.5% yttrium-stabilized zirconium oxide, 0.6% zinc stearate, and 0.4% hydroquinone.

[0175] The preparation of the coated sand, the materials for preparing the modified phenolic resin, and the preparation of the modified phenolic resin are the same as in Example 1.

[0176] 3. Comparative Example 3

[0177] Difference from Example 3: Insufficient vacuum, all other conditions are the same.

[0178] Shell making: Prepare coated sand and make the shell at a temperature of 240℃.

[0179] Shell packing: steel shot diameter 1.5mm, vibration compaction for 40s.

[0180] Melt casting: Casting material formulation (wt%): C: 3.1%, Si: 3.2%, Mn: 0.7%, Ni: 1.1%, Cu: 1.3%, Mo: 0.4%, S: 0.09%, P: 0.13%, Y: 0.10%, Ce: 0.12%, La: 0.03%, Nd: 0.02%, total rare earth 0.27%; 0.8% chromium nitride (N content 0.09%) added, balance Fe. Heating rate 60℃ / min, vacuum degree 0.07MPa, pouring temperature 1370℃, vacuum holding pressure 15min.

[0181] Casting removal: Sandblasting pressure 0.4MPa, sand particle diameter 0.2mm.

[0182] Coated sand formulation (wt%): 84% 100-mesh chromite sand, 6.5% modified phenolic resin, 3.0% nano alumina sol, 1.2% hexagonal boron nitride, 0.8% titanate coupling agent, 2.0% silicon carbide whiskers, 1.5% yttrium-stabilized zirconium oxide, 0.6% zinc stearate, and 0.4% hydroquinone.

[0183] The preparation of the coated sand, the materials for preparing the modified phenolic resin, and the preparation of the modified phenolic resin are the same as in Example 1.

[0184] III. Single-factor experiments

[0185] 1. The effect of metal template heating temperature on casting properties

[0186] Group Heating temperature (°C) Salt spray corrosion resistance rate (mm / a) Dimensional tolerances (mm) Tensile strength (MPa) Comparison Group 1 150 0.05 ±0.18 411 Comparison Group 2 170 0.02 ±0.08 456 Example 3 230 0.02 ±0.07 462 Comparison Group 3 290 0.03 ±0.10 433 Comparison Group 4 310 0.06 ±0.16 406

[0187] Analysis: Below 170℃, the coated sand does not fully solidify, resulting in low shell strength, easy deformation, large dimensional tolerances, low density, and decreased corrosion resistance and strength in the castings. Above 290℃, the modified phenolic resin undergoes excessive aging and decomposition, leading to poor shell permeability, hindered molten iron filling, increased casting defects, and decreased performance. The optimal temperature range is 170-290℃, with 230℃ being the best.

[0188] 2. The effect of pouring temperature on casting properties

[0189] Group Pouring temperature (°C) Salt spray corrosion resistance rate (mm / a) Dimensional tolerances (mm) Tensile strength (MPa) Comparison Group 1 1330 0.05 ±0.17 405 Comparison Group 2 1350 0.03 ±0.10 439 Example 3 1370 0.02 ±0.07 462 Comparison Group 3 1400 0.02 ±0.08 456 Comparison Group 4 1420 0.06 ±0.15 413

[0190] Analysis: When the temperature is below 1350℃, the molten iron lacks fluidity, resulting in insufficient filling and defects such as incomplete filling and cold shuts in the casting, leading to decreased performance. When the temperature is above 1400℃, the molten iron exerts a large thermal shock on the shell mold, making the shell mold prone to cracking. This increases sand adhesion and sand holes in the casting, reducing corrosion resistance and strength. The optimal temperature range is 1350-1400℃, with 1370℃ being the best.

[0191] 3. Effect of modified phenolic resin dosage on casting properties

[0192] Group Modified phenolic resin dosage (wt%) Salt spray corrosion resistance rate (mm / a) Dimensional tolerances (mm) Tensile strength (MPa) Comparison Group 1 5 0.06 ±0.19 393 Comparison Group 2 6 0.02 ±0.08 452 Example 3 6.5 0.02 ±0.07 462 Comparison Group 3 7 0.03 ±0.10 434 Comparison Group 4 8 0.07 ±0.17 403

[0193] Analysis: When the resin content is below 6%, the bonding strength is insufficient, the shell strength is low, it is easily broken, and the casting has poor dimensional accuracy and low density. When the resin content is above 7%, excessive resin leads to poor shell permeability, making it difficult for gas to escape during molten iron filling, forming pores, and increasing the high-temperature decomposition products of the resin, which affects the performance of the casting. The optimal dosage range is 6-7%, with 6.5% being the best.

[0194] 4. Effect of nano-alumina sol dosage on casting properties

[0195] Group Amount of nano-alumina sol (wt%) Salt spray corrosion resistance rate (mm / a) Dimensional tolerances (mm) Tensile strength (MPa) Comparison Group 1 2 0.05 ±0.18 418 Comparison Group 2 2.5 0.03 ±0.10 437 Example 3 3.0 0.02 ±0.07 462 Comparison Group 3 3.5 0.02 ±0.08 453 Comparison Group 4 4 0.06 ±0.16 402

[0196] Analysis: When the dosage is below 2.5%, the filling effect is insufficient, the shell density is low, the thermal shock resistance is poor, and the casting performance is reduced; when the dosage is above 3.5%, excessive sol leads to increased shell brittleness, making it prone to cracking due to thermal shock, affecting the casting quality. The optimal dosage range is 2.5-3.5%, with 3.0% being the best.

[0197] 5. The effect of total rare earth element content on casting performance

[0198] Group Total usage of rare earth elements (wt%) Salt spray corrosion resistance rate (mm / a) Dimensional tolerances (mm) Tensile strength (MPa) Comparison Group 1 0.1 0.04 ±0.12 423 Comparison Group 2 0.2 0.03 ±0.10 447 Example 3 0.27 0.02 ±0.07 462 Comparison Group 3 0.4 0.02 ±0.08 452 Comparison Group 4 0.6 0.05 ±0.14 415

[0199] Analysis: When the total usage is below 0.2%, the purification and oxide film formation effects of rare earth elements are insufficient, resulting in poor corrosion resistance and mechanical properties of the castings. When the total usage is above 0.4%, excessive rare earth elements easily form brittle phases, reducing the toughness and strength of the castings and increasing costs. The optimal total usage range is 0.2-0.4%, with 0.27% being the best.

[0200] Group Salt spray corrosion resistance rate (mm / a) Dimensional tolerances (mm) Tensile strength (MPa) Tensile strength at 600℃ (MPa) Surface roughness Ra (μm) Example 1 0.02 ±0.08 454 362 1.2 Example 2 0.03 ±0.10 437 345 1.5 Example 3 0.02 ±0.07 462 376 1.1 Example 4 0.025 ±0.09 445 355 1.3 Example 5 0.03 ±0.08 455 365 1.4 Comparative Example 1 0.09 ±0.16 409 303 2.1 Comparative Example 2 0.07 ±0.21 382 275 2.6 Comparative Example 3 0.06 ±0.19 394 297 1.9

[0201] Performance Analysis:

[0202] 1. Performance comparison of the examples:

[0203] Example 3 exhibits the best overall performance, with the lowest salt spray corrosion rate, smallest dimensional tolerance, and highest tensile strength. This is because the rare earth elements in this group of casting materials work synergistically in proportion to form stable nitrides with nitrogen elements. Furthermore, the high proportion of chromite sand in the coated sand enhances high-temperature resistance and, together with additives, improves shell stability, ultimately enhancing the casting performance.

[0204] 2. Analysis of Comparative Example 1:

[0205] The lack of rare earth elements and nitrogen significantly reduces the corrosion resistance of castings due to the loss of the dense oxide film of y, the grain boundary purification of ce, and the strengthening effect of nitrogen nitrides. At the same time, the dimensional tolerance increases and the strength decreases, indicating that the synergistic effect of rare earth elements and nitrogen is crucial for refining the microstructure and stabilizing the structure.

[0206] 3. Analysis of Comparative Example 2:

[0207] Quartz sand has a much lower refractoriness than chromite sand. Chromite sand has a refractoriness of >1800℃, while quartz sand has a refractoriness of <1700℃. At high temperatures, quartz sand is prone to softening and deformation, which can lead to shell collapse, sand adhesion in castings, increased dimensional tolerances, and a significant reduction in corrosion resistance and strength.

[0208] 4. Analysis of Example 3:

[0209] When the pouring temperature is 1300℃, which is lower than the optimal range (1350-1400℃), the molten iron has insufficient fluidity and is not filled sufficiently. This results in micro-shrinkage cavities in the casting, reduced density, increased salt spray corrosion resistance, decreased tensile strength, and poor dimensional accuracy due to poor filling.

[0210] The above description, in conjunction with preferred embodiments, provides a further detailed explanation of the present invention and should not be construed as limiting the specific implementation of the invention to these descriptions. For those skilled in the art, various substitutions or modifications can be made to these described embodiments without departing from the inventive concept, and all such substitutions or modifications should be considered within the scope of protection of the present invention.

[0211] Although the invention and its advantages have been described in detail, it should be understood that various changes, substitutions, and modifications can be made without departing from the spirit and scope of the invention. Furthermore, the scope of the invention is not limited to the specific embodiments of the processes, manufactures, compositions of matter, methods, and steps described in the specification. From the disclosure of this invention, those skilled in the art will readily utilize existing or future processes, manufactures, compositions of matter, methods, or steps that substantially perform the same function or achieve the same results as the corresponding embodiments described herein. Therefore, the appended claims are intended to encompass such processes, machines, manufactures, compositions of matter, methods, or steps.

Claims

1. A method for producing high-precision corrosion-resistant castings using shell casting, characterized in that, Includes the following steps: S1. Shell Formation: Prepare coated sand and evenly cover it on a metal template. Heat the metal template to create an upper shell and a lower shell. Then, bond and integrate the upper and lower shells to form a complete shell. S2. Shell Packing: Place the prepared shell into the box, fill the gap between the outside of the shell and the inner wall of the box with steel shot, and use vibration to make the steel shot fully compacted. S3, Melting and Casting: The casting material is melted into molten iron under vacuum and poured into the inner cavity of the shell mold. After pouring, it is cooled to form the casting. S4. Casting Removal: Pour out the castings, waste sand, and steel shot from the box. After separating the castings, clean and inspect the surface of the castings. Once qualified, they are put into storage.

2. The method for producing high-precision corrosion-resistant castings by shell casting according to claim 1, characterized in that, The casting material composition, by mass percentage, includes: C: 2.5-3.5%, Si: 2.5-3.5%, Mn: 0.6-0.8%, Ni: 0.5-1.0%, Cu: 1.0-1.5%, Mo: 0.3-0.5%, Cr: 3-5%, N: 0.05-0.1%, S≤0.1%, P≤0.15%, total rare earth elements 0.1-0.5%, with the balance being Fe; wherein the rare earth elements include Y, Ce, La, and Nd, with N added in the form of chromium nitride intermediate alloy.

3. The method for producing high-precision corrosion-resistant castings by shell casting according to claim 2, characterized in that, The mass percentages of each component in the rare earth elements are as follows: Y accounts for 30-40% of the total rare earth content, Ce accounts for 35-45%, La accounts for 10-20%, and Nd accounts for 10-20%.

4. The method for producing high-precision corrosion-resistant castings by shell casting according to claim 1, characterized in that, In step S1, the coated sand comprises, by mass percentage: 80-90% chromite sand, 6-7% modified phenolic resin, 2.5-3.5% nano-alumina sol, 1.0-1.5% hexagonal boron nitride, 0.7-1.0% titanate coupling agent, 1.5-2.5% silicon carbide whiskers, 1.2-1.8% yttrium-stabilized zirconium oxide, 0.4-0.8% zinc stearate, and 0.3-0.5% hydroquinone.

5. The method for producing high-precision corrosion-resistant castings by shell casting according to claim 4, characterized in that, The particle size of chromite sand is 50-200 mesh.

6. The method for producing high-precision corrosion-resistant castings by shell casting according to claim 1, characterized in that, In step S3, during the process of melting into molten iron, a medium-frequency induction furnace is used for heating at a heating rate of 50-80℃ / min.

7. The method for producing high-precision corrosion-resistant castings by shell casting according to claim 1, characterized in that, In step S1, the heating temperature of the metal template is controlled between 170-290℃.

8. The method for producing high-precision corrosion-resistant castings by shell casting according to claim 1, characterized in that, In step S3, the pouring temperature of the molten iron is controlled at 1350-1400℃.

9. The method for producing high-precision corrosion-resistant castings by shell casting according to claim 1, characterized in that, In step S2, the particle size of the steel shot is 0.5-2 mm.

10. The application of the method according to any one of claims 1-9 in the production of chemical equipment parts and marine engineering equipment parts.